ENT 530 Social Media Portfolio: TFN brownies by Yasmin / Yasmin Azra Shaheezam - Shaheezam, Yasmin Azra (2021)
TFN brownies by Yasmin is selling thin brownies that is new to the market. It is the thinnest brownies in the market, perfect as an on-the-go snack. Currently TFN brownies are selling a variety of 3 flavoured thin brownies which are Chocolate Chip, Walnut and Mint. Consumers have a choice of 3 different flavour to choose from according to their preferences. The price of TFN brownies starts at a price of RM12 for a packet and this price is affordable for all range of consumer’s incomes. Everyone loves brownies, however the traditional brownies that we eat can be quite heavy sometimes when you are just looking for a sweet snack to eat. TFN brownies by Yasmin offers brownies that are created thin and easy for people to consume.The objectives is to produce a snack that is suitable for every situation. With a convenient packaging and size, this snack is also perfect for consumers who are on the move.